Benzopyrazine derivatives: A novel class of growth factor receptor bound protein 7 antagonists - Ambaye, Nigus D.; Gunzburg, Menachem J.; Lim, Reece C.C.; Price, John T.; Wilce, Matthew C.J.; Wilce, Jacqueline A. (Bioorganic & medicinal chemistry, 2011)
A succession of computational ligand design regimes followed by experimental binding affinity measurements was conducted to identify a novel class of Grb7 antagonists. Growth factor receptor bound protein 7 (Grb7) is an adapter protein that functions as a downstream effector of growth factor mediated signal transduction. Over-expression of Grb7 has been implicated in a variety of cancers such as breast, blood, pancreatic, esophageal, and gastric carcinomas. Inhibition of Grb7 has been shown to reduce the migratory and proliferative potential of these cancers, making it an attractive therapeutic target. Starting with a known peptide antagonist, the present work reports the application of a succession of computational ligand design tools comprising a ligand shape based similarity search, molecular docking and a 2D-similarity search to identify small molecular antagonists of the Grb7-SH2 domain from the NCI chemical database. Binding to the Grb7-SH2 domain was then experimentally tested using melting point shift assays and isothermal titration calorimetry. Overall, a total of 11 benzopyrazine based small molecular antagonists were identified with affinity for the Grb7-SH2 domain. Representative compounds tested using ITC were revealed to possess moderate binding affinity in the low micromolar range. Finally, the lead compound (NSC642056) was found to reduce the growth of a Grb7-expressing breast cancer cell line with an IC50 of 86μM. It is expected that the identified antagonists will be useful additions to further explore the function of Grb7 and for the development of inhibitors with therapeutic potential.